Acute radiotherapy toxicity in 57 dogs with gross and microscopic mast cell tumours. (15th May 2018) - Blackwood, L.; Tanis, J. B.; Harper, A.; Amores‐Fuster, I.; Killick, D. R.; Finotello, R.
Abstract : Mast cell tumours (MCTs) are commonly treated with radiation therapy, most often in a microscopic disease setting. Poorer outcomes are expected in patients with gross disease, and irradiation of gross disease may be associated with greater toxicity. The aim of this study was to compare acute radiation adverse events (AE) in dogs with gross and microscopic MCTs receiving radiotherapy. Fifty‐seven dogs were included, 28 with gross disease and 29 with microscopic. In order to assess mucosal and skin toxicity, patients were assigned to 2 groups: head (29 patients, 14 patients with gross and 15 microscopic) and other sites (28 patients, 14 each). All were treated with external beam radiotherapy, and toxicity assessed at the end of treatment and 10 to 14 days later (first recheck). All patients developed some acute radiation toxicity by the end of the course. However, there was no difference in the severity of toxicity between gross and microscopic disease in either site group at either time point. The only variable associated with an increased frequency of grade 2 or 3 toxicity at the first recheck was the use of prednisolone prior to radiotherapy ( P  = .05). No other factors were identified which were associated with increased toxicity. For the head group, the site of highest grade toxicity was mucosa or, if included in the field, nasal planum, which was often more severely affected than the mucosa. No significant late toxicity was identified. Two dogs developed acute haematemesis during the radiotherapy course, but both completed the course without further events.